Exploring antiretroviral treatment discontinuation among people living with HIV in Indonesia: A qualitative study - Sujianto, Untung; Amirudin, Ikhwan; Akbar, M Agung; Waluyo, Agung; Nursasi, Astuti Yuni (Belitung Nursing Journal, 2025)
Background: Discontinuation of antiretroviral therapy (ART) among people living with HIV (PLHIV) presents significant challenges for HIV care, often leading to physical deterioration, emotional distress, and social isolation. Although prior studies have addressed barriers to adherence, little is known about the experiences of PLHIV following treatment discontinuation in the Indonesian context. Objective: To explore the experiences of Indonesian PLHIV who have discontinued ART. Methods: This qualitative study employed a descriptive phenomenological approach and was conducted in three urban areas of Indonesia (Jakarta, Yogyakarta, and Bandar Lampung) between August and September 2024. Fifteen participants were purposively recruited from community-based organizations. In-depth semi-structured interviews were conducted, transcribed verbatim, and analyzed using Colaizzi’s method to identify themes and meanings in the narratives. Results: Three major themes emerged: (1) Physical and psychological consequences of ARV discontinuation, including fatigue, anxiety, and a sense of losing control; (2) Prolonged social strain and stigma, marked by loss of support and moral judgment from others; and (3) Searching for meaning and coping without treatment, including spiritual resignation and detachment from bodily control. These themes reflect the complex, multidimensional burdens PLHIV face after stopping treatment, particularly in the Indonesian context, where HIV stigma is deeply rooted in sociocultural and religious norms, and access to mental health support remains limited. Conclusion: ART discontinuation is not merely a clinical event but a deeply human experience shaped by physical decline, emotional conflict, social rejection, and existential adaptation. To improve long-term HIV care outcomes, healthcare systems must integrate psychosocial and spiritual support for individuals who disengage from treatment, encouraging re-engagement through nonjudgmental and person-centered care. For nursing practice, this study emphasizes the importance of developing empathetic communication, providing culturally sensitive counseling, and actively addressing stigma during care interactions.